Nanocrystalline Al Composites from Powder Milled under Ammonia Gas Flow - J. Cintas; E. S. Caballero; J. M. Montes; F. G. Cuevas; C. Arevalo (Advances in Materials Science and Engineering)
The production of high hardness and thermally stable nanocrystalline aluminium composites is described. Al powder was milled at room temperature in an ammonia flow for a period of less than 5 h. NH3 dissociation during milling provokes the absorption, at a high rate, of nitrogen into aluminium, hardening it by forming a solid solution. Controlled amounts of AlN and Al5O6N are formed during the subsequent sintering of milled powders for consolidation. The pinning action of these abundant dispersoids highly restrains aluminium grain growth during heating. The mean size of the Al grains remains below 45 nm and even after the milled powder is sintered at 650°C for 1 h.